Association between facial nerve second genu angle and facial canal dehiscence in patients with cholesteatoma: evaluation with temporal multidetector computed tomography and surgical findings - TanrivermiŞ Sayit,Asli (2019)
Abstract Introduction: Otitis media, mastoiditis or the pressure effect of tumorous lesions such as cholesteatoma can be the cause of facial canal dehiscence and facial nerve paralysis. The most common segment involved in dehiscence is the tympanic segment and the second most common is the lateral aspect of the facial canal in the oval window area. Objective: To determine the prevalence of the facial canal dehiscence and the relationship between the angle at the second genu of the facial nerve and facial canal dehiscence. Methods: We evaluated the surgical findings in 113 patients who underwent surgery for cholesteatoma. Facial canal dehiscence was detected in 62 of the 113 patients. Patients were divided into two groups: Group 1, with dehiscence of the facial canal and Group 2, without dehiscence of the facial canal. Results: The mean angles at the second genu of the facial nerve in Groups 1 and 2 were 117.8º ± 9.63º and 114º ± 9.9º, respectively. There was a statistically significant difference between the mean angles at the second genu for the two groups (p = 0.04). Conclusion: In patients with dehiscence of the facial canal, the angle at the second genu was found to be wider than those without dehiscence.